2014
DOI: 10.1371/journal.pone.0083779
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Associated Symbiotic Burkholderia Species Lack Hallmark Strategies Required in Mammalian Pathogenesis

Abstract: Burkholderia is a diverse and dynamic genus, containing pathogenic species as well as species that form complex interactions with plants. Pathogenic strains, such as B. pseudomallei and B. mallei, can cause serious disease in mammals, while other Burkholderia strains are opportunistic pathogens, infecting humans or animals with a compromised immune system. Although some of the opportunistic Burkholderia pathogens are known to promote plant growth and even fix nitrogen, the risk of infection to infants, the eld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
107
1
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(124 citation statements)
references
References 66 publications
7
107
1
9
Order By: Relevance
“…Similarly, Angus et al (2014) analyzed the genomes of several Burkholderia species using functional and genomic methods to determine whether virulence determinants could be found in Group A species. Their genomics analysis showed that many of the Group A strains lack the Type 3 secretion system, especially T3SS-3, which is responsible for B. pseudomallei virulence in mammalian hosts.…”
Section: Nitrogen Fixation and Legume Nodulation In Burkholderia Speciesmentioning
confidence: 99%
“…Similarly, Angus et al (2014) analyzed the genomes of several Burkholderia species using functional and genomic methods to determine whether virulence determinants could be found in Group A species. Their genomics analysis showed that many of the Group A strains lack the Type 3 secretion system, especially T3SS-3, which is responsible for B. pseudomallei virulence in mammalian hosts.…”
Section: Nitrogen Fixation and Legume Nodulation In Burkholderia Speciesmentioning
confidence: 99%
“…To address the safety concerns, a study of the pathogenic potential of plant-associated symbiotic species of the genus Burkholderia was conducted, resulting in the conclusion that it is highly unlikely that they can infect mammals (Angus et al, 2014), but the study results did not seem to be sufficiently convincing . It was argued that strains of some species from the second group, such as strains of Burkholderia fungorum isolated from various human and veterinary clinical samples, might be opportunistic pathogens.…”
mentioning
confidence: 99%
“…B. thailandensis is used as a less virulent model for the select agents B. pseudomallei and B. mallei, the causative agents of melioidosis and glanders, respectively. The reduced virulence of B. thailandensis is due primarily to the absence of the major capsule locus, important for B. pseudomallei virulence in mammals (4), although it is used to study the effect of type III secretion systems on phagocytic escape and retains other genes associated with virulence (5,6). Despite virulence differences, a great deal of the core genome is shared between B. thailandensis and its relatives, including many pathways for accessory metabolism.…”
mentioning
confidence: 99%